Psychopathologic symptoms in post-myocardial infarction patients - Olajossy, Marcin; Koprianiuk, Agata (Current Problems of Psychiatry, 2011)
The study aimed to assess severity/features of psychopathologic symptoms in post-myocardial infarction patients in comparison to clinically healthy people. Study group and methods: Research was conducted in a group of 60 people. Clinical group included 30 patients (60% of males and 40% of females) after first myocardial infarction and 30 healthy people (control group). All the patients were assessed using sociodemographic questionnaire worked out by the authors and Hopkins Symptom Checklist (HSCL). Results and conclusions: Based on obtained results the following conclusions were made: 1. Patients after myocardial infarction showed higher results in all scales contained in HSCL Questionnaire in comparison to healthy people. 2. Depression is the dominating psychopathological symptom in post-myocardial infarction patients.